Investigations of solvatochromism of 2-(3-coumaroyl)-benzopyrylium dye and its di-substituted derivatives - Sanin, E.V.; Novikov, A.I.; Roshal, A.D. (Functional Materials, 2013)
The electronic structure of 2-(3-coumaroyl)-benzopyrylium perchlorate (CBP) and its di-substituted derivatives, has been investigated the experimental and theoretical analysis of spectral properties of these compounds in various media. It was found that spectral behavior of CBP and its derivatives depend on two solvent properties – nucleophility, which stabilizes cations in the ground state, and polarizability, which stabilizes cations in the Frank-Condon excited state. The growth of nucleophility and polarizability parameters of solvents leads, correspondingly, to hypsochromic and bathochromic shifts of CBP long-wavelength absorption bands. Spectral manifestations of the solvent nucleophility appear in CBP derivatives with strong inter-fragmental charge transfer upon excitation resulting in substantial delocalization of the positive charge.